2016
DOI: 10.1038/ncomms11837
|View full text |Cite
|
Sign up to set email alerts
|

Observing the release of twist by magnetic reconnection in a solar filament eruption

Abstract: Magnetic reconnection is a fundamental process of topology change and energy release, taking place in plasmas on the Sun, in space, in astrophysical objects and in the laboratory. However, observational evidence has been relatively rare and typically only partial. Here we present evidence of fast reconnection in a solar filament eruption using high-resolution H-alpha images from the New Vacuum Solar Telescope, supplemented by extreme ultraviolet observations. The reconnection is seen to occur between a set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(96 citation statements)
references
References 59 publications
(76 reference statements)
8
82
3
2
Order By: Relevance
“…We outline the path of the inflow and repeated 10 times to get the uncertainty error bars. The inflow velocities evaluated in the letter are much larger than that of the inflows observed in some previous literatures (e.g., several km s −1 , Yokoyama et al 2001;Sun et al 2015;Xue et al 2016) and a little smaller than the inflows from 150 to 690 km s −1 reported by Savage et al (2012a). Comparing the event in this letter and that studied by Savage et al (2012a) with other events, we found that the inflow in the events with an erupting flux rope is distinctly larger than that without an erupting flux rope.…”
Section: Resultsmentioning
confidence: 40%
See 1 more Smart Citation
“…We outline the path of the inflow and repeated 10 times to get the uncertainty error bars. The inflow velocities evaluated in the letter are much larger than that of the inflows observed in some previous literatures (e.g., several km s −1 , Yokoyama et al 2001;Sun et al 2015;Xue et al 2016) and a little smaller than the inflows from 150 to 690 km s −1 reported by Savage et al (2012a). Comparing the event in this letter and that studied by Savage et al (2012a) with other events, we found that the inflow in the events with an erupting flux rope is distinctly larger than that without an erupting flux rope.…”
Section: Resultsmentioning
confidence: 40%
“…Besides, a clear reconnection inflow and X-point were found in a limb flare on 1999 March 18 (Yokoyama, Yamamot & Fukao 2001). With the development of the observational technology, more and more features of magnetic reconnection were reported (Savage et al 2010;Liu et al 2010;Zhang et al 2012;Sun et al 2012;Savage et al 2012aSavage et al , 2012bSu et al 2013;Zhang et al 2013;Deng et al 2013;Dudík et al 2014;Tian et al 2014;Yang, Zhang & Xiang 2015;Sun et al 2015;Xue et al 2016;Li et al 2016;Zhu et al 2016;Li et al 2017;Shen et al 2017). Furthermore, many simulations also show evidence that magnetic reconnection plays an important role in solar eruptions (Antiochos et al 1999, Chen & Shibata 2000, Amari et al 2003, Aulanier et al 2010, Janvier et al 2013Ni et al 2016Ni et al , 2017Mei et al 2017;Jiang et al 2016Jiang et al , 2017.…”
Section: Introductionmentioning
confidence: 93%
“…Dynamical events, such as chromospheric jets (e.g., Liu et al 2009;Morton 2012;Bharti et al 2013;Tian et al 2014), Ellerman Bombs (e.g., Fang et al 2006;Hong et al 2014;Nelson et al 2015) and type II white light flares (e.g., Ding et al 1994Ding et al , 1999, are all related to magnetic reconnection in the partially ionized low atmosphere. Improvements in the angular resolution of solar telescopes have allowed many small scale magnetic reconnection events in the low solar atmosphere to be observed (e.g., Yang et al 2015;Xue et al 2016;Zhao et al 2017). The high temperature compact bright points which have UV counterparts that are frequently observed with the Interface Region Imaging Spectrograph (IRIS) (Peter et al 2014;Vissers et al 2015;Grubecka et al 2016;Tian et al 2016) are known as IRIS bombs.…”
Section: Introductionmentioning
confidence: 99%
“…The eruption process of this case was studied by Xue et al (2016), who suggested a internal reconnection occurring between the ambient fibrils and the filament itself to relax magnetic tension during the eruption. From a different perspective, here we focus on the whole process, especially the role of EMR, before the eruption.…”
Section: Observations and Resultsmentioning
confidence: 99%
“…It is reasonable that the west part of the filament erupted first according to the model of torus instability. When the eruption began, the untwisting motion of the filament was explained by Xue et al (2016) as a reconnection occurring between the ambient fibrils and the filament to relax magnetic tension.…”
Section: Discussionmentioning
confidence: 99%